Plant Silicon Interactions between Organisms and the Implications for Ecosystems - Jane L. DeGabriel (Frontiers Research Topics, 2017)
In this Frontiers topic, we explore how the functions and fates of plant silicon interact with other organisms and ecosystem processes. By bringing together new data from multiple disciplines and scales, we present a cross-section of novel explorations into how plants use silicon and the implications for agriculture and ecosystems. Key aims in this field are to understand the determinants of plant silicon uptake and cycling, and the benefits that silicon uptake confers on plants, including reducing the impacts of stresses such as herbivory. Current research explores inter-specific interactions, including co-evolutionary relationships between plant silicon and animals, particularly morphological adaptations, behavioural responses and the potential for plant silicon to regulate mammal populations. Another emerging area of research is understanding silicon fluxes in soils and vegetation communities and scaling this up to better understand the global silicon cycle. New methods for measuring plant silicon are contributing to progress in this field. Silicon could help plants mitigate some effects of climate change through alleviation of biotic and abiotic stress and silicon is a component of some carbon sinks. Therefore, understanding the role of plant silicon across ecological, agricultural and biogeochemical disciplines is increasingly important in the context of global environmental change.